2020
DOI: 10.1101/2020.12.16.423117
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Under-Oil Autonomously Regulated Oxygen Microenvironments: A Goldilocks Principle-Based Approach For Microscale Cell Culture

Abstract: Oxygen levels in vivo are autonomously regulated by a supply-demand balance, which can be altered in disease states. However, the oxygen levels of in vitro cell culture systems, particularly microscale cell culture, are typically dominated by either supply or demand. Further, the oxygen microenvironment in these systems are rarely monitored or reported. Here, we present a method to establish and dynamically monitor autonomously regulated oxygen microenvironments (AROM) using an oil overlay in an open microscal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 71 publications
(130 reference statements)
0
11
0
Order By: Relevance
“…Specifically in the under-oil approach, we use fluorinated oil and/or silicone oil as the oil barrier, which minimizes oil extraction of lipophilic molecules [see the ultra-performance liquid chromatography-tandem mass spectrometer (UPLC-MS) characterization in our previous publication]. 31 The volume of oil required in UOMS-AST is small as long as enough to cover the sessile droplets on a device. For example, to cover the whole surface and sessile droplets in the 1-well chambered coverglass, we only need 1 to 2 mL of the oil.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Specifically in the under-oil approach, we use fluorinated oil and/or silicone oil as the oil barrier, which minimizes oil extraction of lipophilic molecules [see the ultra-performance liquid chromatography-tandem mass spectrometer (UPLC-MS) characterization in our previous publication]. 31 The volume of oil required in UOMS-AST is small as long as enough to cover the sessile droplets on a device. For example, to cover the whole surface and sessile droplets in the 1-well chambered coverglass, we only need 1 to 2 mL of the oil.…”
Section: Resultsmentioning
confidence: 99%
“…5, and see details in our previous publications), 25,29 and iii) autonomously regulated oxygen microenvironments (AROM), where cells spontaneously set up, regulate, and respond to the oxygen kinetics via a supply-demand balance as seen in vivo (see details in our previous publication). 31 Studies have shown the broad impact of hypoxia on microbial infection and pathogenesis. 43,44 The double-oil conditions (i.e., one oil plus another oil) showed the flexibility of adjusting the oil overlay by combining the properties of two oil types, e.g., different diffusion coefficients of vital gases (e.g., O 2 and/or CO 2 ), 31 or under-oil media evaporation/loss rate.…”
Section: Integration With Cloud Lab For Real-time Image Analysis and ...mentioning
confidence: 99%
See 3 more Smart Citations